Standar Bahasa yang Benar antara Bahasa dan Sintak - Muhammad Zakki Masykur (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
Language is regularly and systematically used by the language user. Basically, language is spoken utterance, verbal arbiter, symbol, symbol, and the signs used in language contain meaning related to life situation and real human experience. If given the understanding of the language, there will be differences of opinion among the linguists. This happens because so wide the scope of the language itself. The development that occurs in the community will also affect the development of the language itself. In its development language requires a method of language itself. And should the standard language itself. How to standard the correct language itself. Whether hasrus corresponds to nahwu, or there is a measure of its own. Departing from this problem we are from a group of 2 modern linguistic courses and its application to Arabic language learning will discuss about the correct language standard between language and nahwu.